The Educational Function of English Children’s Movies From the Perspective of Multiculturalism Under Deep Learning and Artificial Intelligence - Hu, Nan; Li, Shuyi; Li, Luna; Xu, Hui (Frontiers in Psychology, 2022)
In children's learning subjects, English courses has its relative particularity compared with Chinese courses and the mathematics. Children's English teaching is often inefficient because of the lack of students’ timely consolidation after class. Given this, the present work starts with the analysis of the current situation of children's learning, and introduces the film-assisted English teaching. In the specific teaching links, English teaching is carried out in a three-dimensional teaching mode. Before that, topics of the films are selected for the English teaching, and the films are edited and processed. Initially, the present work expounds the English children's films and their educational functions. Then, children can obtain teaching effect from the films. An English questionnaire is designed to analyze the application effect of English films in children's English teaching. The results show that the film teaching mode improves children's learning interest and motivation, and English film teaching can stimulate students' learning interest. Students are also more active to participate in teaching activities, thus mproving their language skills. Under the teaching in the scenes of films, students can perceive the functions of language in certain contexts. Comprehensible language input promotes students' English listening ability and oral expression ability. The films can intuitively show the humanistic style, historical geography, cultures, and customs of English countries, and then cultivate students' western cultural literacy. Practice has proved that the method proposed here can achieve good teaching effect, and it provides certain references for children's English education.